Education and training in general and teacher training in particular - Martínez Ramírez, Carlos Alberto (IE Revista de Investigación Educativa de la REDIECH, 2024)
Teacher training is one of the most significant challenges in the educational system. Teachers have diverse life stories, profiles, and academic, professional and work experiences that impact their daily practice and interaction with students. Teacher training, specifically, is immersed in debates, contributions, criticisms, and proposals that emphasize the central role of teachers; however, there are other levels of responsibility beyond them: family, educational and school authorities, and the students themselves. Those dedicated to this noble profession face a series of perspectives, identity processes, self-reflections, changes, demands and complex realities. This essay highlights various reflections on what education implies, viewed as a human and social process, without losing sight of its theoretical, historical and epistemic construction. The perspective of multi-referential training posed by Jacques Ardoino is also considered. Finally, the essay explores how these overarching concepts, education and training, contribute to distinguishing the importance and theoretical and experiential evolution of teacher training in the educational sphere.